Development of Sansevieria Trifasciata Fibre (STF) reinforced concrete / Nur Akmal Saidah Jamat and Azamuddin Husin - Jamat, Nur Akmal Saidah; Husin, Azamuddin (2023)
Environmental issues caused by the industrial pollution of synthetic fibre pose a major challenge in today’s world. Synthetic fibres are non-biodegradable, making them hard to disintegrate. To overcome this problem, an alternative material can serve as a viable substitute for synthetic fibres. Simultaneously, cracking is a common issue in concrete. There is a need to develop methods that reduce crack progression. The lack of research on the mechanical performance of concrete with STF prompted this study. The study aims to evaluate the mechanical performance of grade M30 concrete with the addition of STF. The objectives are to determine the best composition of concrete mix with STF, develop the prototype of concrete slab, and identify the marketability potential of the concrete with STF. The compressive test and density test of hardened concrete were conducted to evaluate the concrete performance. A compressive test was conducted at 7 and 28 days on three manipulated samples containing 0.25% STF, 0.5% STF, and 0.75% STF, each with a constant length of 30 millimetres.